Estratégia competitiva entre Biomphalaria glabrata e Biomphalaria tenagophila: estudos de laboratório - Mairy Barbosa Loureiro dos Santos; José Rabelo de Freitas; Edirce de Souza Resende Alves; Luiz Antônio Rocha (Memorias do Instituto Oswaldo Cruz, 1989)
Observation about conhabitation among B. glabrata and B. tenagophila revealed a greater vulnerability of B. tenagophila population during the process of competition when its density was severaly decreased in 12 trials, moderate in 2 trials. It was higher than B. glabrata in only one trial. Some snail water chemical parameters analysed such as pH, alkalinity, conductivity and oxygen dissolve, an the viability rate of batch of eggs didn't give subsidy to explain the competition mechanism. The newly-born survival, in the situation of cohabitation, was low for both species. This reveals the existence of intra and interspecific competitive interacition. The fertility rate reduction of B. tenagophila during the cohabitation was considered as a cause of its exlusion. One of the factors that seems to have influenced the fertility rate was a possible wrong crossing.